XPS INVESTIGATIONS OF La₀.₆₇Sr₀.₃₃Co₁₋ₓMnₓO₃ COMPOUNDS - DUDRIC, R.; DEAC, Iosif G.; NEUMANN, M.; TETEAN, R. (Studia Universitatis Babeș-Bolyai Physica, 2016)
The electronic structure of the polycrystalline La0.67Sr0.33Co1-xMnxO3 perovskites with 0 ≤ x ≤ 0.5 has been investigated by X-ray photoelectron spectroscopy (XPS). The valence band spectra shows several features, due to Mn 3d, Co 3d and extensively hybridized Mn3d-O2p and Co3d-O2p states, while the core level spectra show the presence of Co4+ and Co2+ states.